Lady Tan's circle of women [compact disc, unabridged] - See, Lisa (Simon & Schuster Audio, 2023)
According to Confucius, "an educated woman is a worthless woman," but Tan Yunxian--born into an elite family, yet haunted by death, separations, and loneliness--is being raised by her grandparents to be of use. Her grandmother is one of only a handful of female doctors in China, and she teaches Yunxian the pillars of Chinese medicine, the Four Examinations--looking, listening, touching, and asking--something a man can never do with a female patient. From a young age, Yunxian learns about women's illnesses, many of which relate to childbearing, alongside a young midwife-in-training, Meiling. The two girls find fast friendship and a mutual purpose--despite the prohibition that a doctor should never touch blood while a midwife comes in frequent contact with it--and they vow to be forever friends, sharing in each other's joys and struggles. No mud, no lotus, they tell themselves: from adversity beauty can bloom. But when Yunxian is sent into an arranged marriage, her mother-in-law forbids her from seeing Meiling and from helping the women and girls in the household. Yunxian is to act like a proper wife--embroider bound-foot slippers, pluck instruments, recite poetry, give birth to sons, and stay forever within the walls of the family compound, the Garden of Fragrant Delights. How might a woman like Yunxian break free of these traditions, go on to treat women and girls from every level of society, and lead a life of such importance that many of her remedies are still used five centuries later? How might the power of friendship support or complicate these efforts?